2020
DOI: 10.1538/expanim.19-0146
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrin ameliorates cognitive deficits, endoplasmic reticulum stress and neuroinflammation in streptozotocin (STZ)-induced Alzheimer’s disease rats

Abstract: Schisandrin, an active component extracted from Schisandra chinensis (Turcz.) Baill has been reported to alleviate the cognitive impairment in neurodegenerative disorder like Alzheimer's disease (AD). However, the mechanism by which schisandrin regulates the cognitive decline is still unclear. In our study, intracerebroventricular injection of streptozotocin (STZ) was employed to establish AD model in male Wistar rats, and indicated dose of schisandrin was further administered. The Morris water maze test was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Moreover, Zhao et al 26 revealed that SCH protects against Aβ 1-42 -induced downregulation of cell viability in SH-SY5Y cells through activation of PI3K/AKT signaling. Song et al 27 indicated that SCH could effectively attenuate the neuroinflammation and cognitive deficits in an streptozotocin-induced AD rat model via inactivation of NF-κB signaling. However, the action mechanism of SCH in AD development remains not fully clear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Zhao et al 26 revealed that SCH protects against Aβ 1-42 -induced downregulation of cell viability in SH-SY5Y cells through activation of PI3K/AKT signaling. Song et al 27 indicated that SCH could effectively attenuate the neuroinflammation and cognitive deficits in an streptozotocin-induced AD rat model via inactivation of NF-κB signaling. However, the action mechanism of SCH in AD development remains not fully clear.…”
Section: Discussionmentioning
confidence: 99%
“…It is proved that ER stress and UPR play an essential role in the occurrence and development of AD (Devi and Ohno, 2014;Duran-Aniotz et al, 2017;Uddin et al, 2020). The related findings, both in vivo and in vitro, have shown that many natural compounds and small molecular inhibitors targeting ER stress and ER stress-mediated neuronal apoptosis contribute to the recovery of AD (Xu et al, 2018;Zhu et al, 2019;Song et al, 2020;Oliveira et al, 2021). However, there are still a lot of questions to be considered if we want to convert these agents into a safe and reliable drug for clinical application, such as the safety, efficacy, and applicability.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Sch A exerts neuroprotective effects in AD progression. Previous study has found that Sch A reduces cognitive disorder of AD mice by inhibiting neuroinflammation, oxidative stress, and endoplasmic reticulum stress (Qi et al 2019;Song et al 2020). Sch A inhibits Ab-mediated neuron damage in AD by activating the PI3K/Akt signalling pathway, and reducing the expression of tau protein (Zhao et al 2019).…”
Section: Introductionmentioning
confidence: 94%
“… 2019 ; Song et al. 2020 ). Sch A inhibits Aβ-mediated neuron damage in AD by activating the PI3K/Akt signalling pathway, and reducing the expression of tau protein (Zhao et al.…”
Section: Introductionmentioning
confidence: 99%